Pore mutation in a G-protein-gated inwardly rectifying K+ channel subunit causes loss of K+-dependent inhibition in weaver hippocampus - Jarolimek, Wolfgang; Bäurle, Jörg; Misgeld, Ulrich (The journal of neuroscience, 1998)
Weaver (wv) mice carry a point mutation in the pore region of a G-protein-gated inwardly rectifying K+ channel subunit (Kir3.2). wvKir3.2 conducts inward currents that may cause the loss of neurons in the cerebellum and substantia nigra. Although Kir3.2 is widely expressed in the CNS, significant morphological or physiological changes have not been reported for other brain areas. We studied the role ofwvKir3.2 in hippocampal slices of young [postnatal day (P) 4-18] and adult wv/wv (≥P24) mice, because protein levels of Kir 3.1 and Kir3.2 appear to be normal in the first 3 postnatal weeks and only decrease thereafter. In disinhibited slices, the GABAB receptor agonist R-baclofen reduced burst activity in wv/wv mice but was much more potent in wild-type mice. Mean resting membrane potential, slope input resistance, and membrane time constant of CA3 neurons of adultwv/wv and wild-type mice were indistinguishable. However, R-baclofen or chloroadenosine did not induce K+ currents or any other conductance change inwv/wv mice. Moreover, electrical or chemical stimulation of inhibitory neurons did not evoke slow IPSPs in adultwv/wv mice. Only in a few cells of youngwv/wv mice did GABAB receptor activation byR-baclofen or presynaptic stimulation induce small inward currents, which were likely caused by a Na+ion influx through wvKir3.2 channels. The data show that the pore mutation in wvKir3.2 channels results in a hippocampal phenotype resembling Kir3.2-deficient mutants, although it is not associated with the occurrence of seizures.